Identification of transgene flanking sequences in a pre-market safety assessed sugarcane in Argentina - Enrique,Ramón (2021)
Abstract: A prerequisite for commercial release of a transgenic crop variety in Argentina and other countries in the world is the identification and sequence analysis of the transgene(s) insertion site in the plant genome. Southern blot analysis showed a high number of transgene inserts in the glyphosate-resistant transgenic sugarcane line TUC 87-3RG. By using a targeted sequence enrichment approach, coupled with second-generation sequencing (SGS) and bioinformatic analyses, we were able to identify and subsequently analyze all flanking sequences for these transgene insertions in the sugarcane genome. PCR reactions confirmed 18 out of 29 candidate contigs as junction sequences that did not match essential genes in published sugarcane genomes. The methodology outlined here represents an efficient strategy for characterization of flanking sequences corresponding to multiple inserts of a transgene in a large, complex, and not fully sequenced plant genome such as that of sugarcane.